Pemberian Edukasi Gizi dan Makanan Bergizi bagi Ibu Hamil dan Anak Balita di Posyandu Kemuning 2 Keturen - Mutiara Rengganis; Riani Febriani Siswanto; Seventina Nurul Hidayah; Nora Rahmanindar; Evi Zulfiana (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
The provision of nutrition education and healthy food for pregnant women and toddlers is crucial in promoting maternal and child health. This project aims to implement a nutrition education program at the Kemuning 2 Keturen Integrated Health Post (Posyandu) to improve the nutritional knowledge and practices of pregnant women and caregivers of toddlers. The project will involve a series of educational sessions conducted by healthcare professionals and trained volunteers. The sessions will cover topics such as the importance of balanced nutrition during pregnancy, appropriate complementary feeding for infants and young children, and the selection of nutritious foods. Visual aids, interactive discussions, and practical demonstrations will be used to enhance the learning experience. Additionally, a nutritious food distribution program will be implemented to provide pregnant women and caregivers of toddlers with access to healthy and affordable food options. Local partnerships will be established with farmers, suppliers, and community organizations to ensure the availability of fresh and nutritious ingredients. The project's success will be evaluated by assessing the participants' knowledge and practices related to maternal and child nutrition before and after the intervention. Feedback from participants and healthcare providers will also be gathered to assess the program's effectiveness and identify areas for improvement. By providing nutrition education and access to healthy food, this project aims to empower pregnant women and caregivers of toddlers in making informed choices regarding their own and their children's nutrition. Ultimately, it is expected to contribute to improved maternal and child health outcomes in the Kemuning 2 Keturen community.